2019
DOI: 10.1101/691857
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DNA end-resection in highly accessible chromatin produces a toxic break

Abstract: Of all damage occurring to DNA, the double strand break (DSB) is the most toxic lesion. Luckily, cells have developed multiple repair pathways to cope with these lesions. These different pathways compete for the same break, and the location of the break can influence this competition. However, the exact contribution of break location in repair pathway preference is not fully understood. We observe that most breaks prefer classical non-homologous end-joining, whereas some depend on DNA end-resection for their r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 81 publications
4
14
0
Order By: Relevance
“…Secondly, we find that CDE+ genes are also enriched for genes whose sgRNAs target highly accessible chromatin (methods; hypergeometric P<0.02), consistent with the findings of a recent work that double-stranded breaks induced in highly accessible chromatin regions could induce stronger DNA damage response 16 .…”
supporting
confidence: 90%
“…Secondly, we find that CDE+ genes are also enriched for genes whose sgRNAs target highly accessible chromatin (methods; hypergeometric P<0.02), consistent with the findings of a recent work that double-stranded breaks induced in highly accessible chromatin regions could induce stronger DNA damage response 16 .…”
supporting
confidence: 90%
“…More importantly, while HR is the preferred pathway that handles DSBs in transcribed chromatin during G2 (Aymard et al, 2014), our data indicate that HR usage is not required to ensure cell viability in this context. This is in agreement with the recent finding that CRISPR/Cas9 induced breaks in DNAse hypersensitive sites (open chromatin) are prone to resection and that inhibiting resection at these DSBs actually improves cell survival (van den Berg et al, 2019). Hence altogether this suggests that DSB in transcribed loci mainly utilizes HR (TAHRR) to ensure accurate repair, but that TAHRR deficiency is not cytotoxic while nevertheless affecting genome stability.…”
Section: Blm and Hencesupporting
confidence: 91%
“…For many years the view that a more open chromatin environment of euchromatin is conducive to HDR and that breaks within transcribed genes are repaired more frequently by HDR has persisted (Aymard et al, 2014; Lemaitre et al, 2014). Indeed a recent study using CRISPR-Cas9 to target specific loci found that open-chromatin may recruit insufficient p53 binding protein 1 (53BP1) (van den Berg et al, 2019), required to promote NHEJ and restrict HDR. Additionally, a more nuanced view has recently arisen in which repair choice is actively directed in different chromatin environments.…”
Section: Chromatin Barriers To Resectionmentioning
confidence: 99%